Projeto e identificação experimental de um protótipo de calibrador de pressão estática e dinâmica - Castro, Romulo Pereira de (2005)
The design methodology and the experimental identification of the dynamic behavior of a pressure calibration system are developed. The calibration device body is a vertical pressure vessel, completely filled with liquid, composed by a rigid tubular structure closed at its both ends by two flexible circular membranes. The lower membrane is used to generate the internal static or dynamic pressure, by applying an external excitation force at its center. The upper membrane acts as a reference pressure sensor, which output is the motion of its center. The pressure transducer to be calibrated is installed close to the upper membrane. The finite element method is used to model the elastic structure and the fluid domain. An acoustic wave formulation model is used to solve the coupled field problem. The fluid-structure interaction occurs at the common interface, in a way that the fluid acoustic pressure exerts a force applied to the structure and the structural motions produce an effective loading at the fluid domain. Modal analysis is performed and frequency responses of the displacement at the center of the upper membrane and the pressure at the face of the transducer to be calibrated are calculated for an harmonic excitation applied at the center of the lower membrane. Tests are conducted on an experimental device using an impulsive excitation force. The velocity at the center of the upper membrane is measured by a laser vibrometer, a piezoelectric load cell measures the excitation force, and a piezoresistive transducer measures the pressure. The obtained results are used to validate the static and the dynamic behavior of the computational model. The influence of the device geometric parameters on its static sensitivity, on the operational frequency band, and on the maximum allowed pressure, are also analysed.